Combining Diffusion-Weighted Imaging Patterns with ABCD2 Score Predicts Stroke Risk after Transient Ischemic Attack - Pei, Lulu; Song, Bo; Fang, Hui; Gao, Yuan; Guo, Yinan; Liu, Kai; Li, Yapeng; Wang, Xiao; Tian, Xuan; Wu, Jun; Sun, Shilei; Xu, Yuming (Current Neurovascular Research, 2018)
Background: Recent studies indicated that multiple acute infarctions on Diffusion- Weighted Imaging (DWI) were associated with a higher risk of stroke. Objective: The study aims to estimate the association of different infarction patterns and ABCD2 score with the prognosis of Transient Ischemic Attack (TIA). Method: We prospectively analyzed the data from TIA database of the First Affiliated Hospital of Zhengzhou University. The predictive outcome was a 90-day ischemic stroke. Cox proportional hazards model was used to evaluate the predictive value of risk factors associated with stroke. The receiver-operating characteristics curves were plotted, and the predictive value was assessed by computing the Area Under the Curve (AUC). Results: A total of 1376 eligible patients were enrolled. DWI patterns were significant predictors for stroke (single acute infarction: hazard ratio [HR] =2.942, p <0.001; multiple acute infarctions: HR =5.552, p <0.001, in comparison with no acute infarction). Patients with both multiple infarctions and ABCD2 ≥4 were associated with approximately 15.5-fold risk of stroke at 90 days (28.8% vs. 2.1%, HR =15.455, 95% confidence interval [CI], 7.946-30.057, p <0.001), compared with those with no infarction or ABCD2 <4. The ABCD2+ DWI patterns showed a better discrimination with an AUC of 0.765 (95% CI, 0.741–0.787) than the ABCD2 score (AUC =0.651; 95% CI, 0.625-0.676; Z =4.777; p <0.0001) and ABCD3-I score (AUC =0.724; 95% CI, 0.700- 0.748; Z =2.697; p =0.007). Conclusion: Combining infarction patterns with ABCD2 score could enhance the predictive value for early stroke risk in TIA.
Keywords: Transient Ischemic Attack (TIA)